Unilateral Actions the Case of International Environmental Problems - Urs Steiner Brandt (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2003)
When abatement costs are uncertain, but correlated, and a country becomes pri-vately informed that costs are low, then unilateral actions serve as a signalling devise to reveal low costs and unilateral actions have the potential to trigger positive responses abroad. However, the country engaging in unilateral actions is the one with the highest expectation about the other countries reactions, and it might suffer from an effect like the winners curse.
Keywords: Q28; H4; D8; 330; International environmental problems; unilateral reductions; signal-ling costs; Internationale Umweltpolitik; Theorie